Early diagnosis of pancreatic cancer: challenges and new developments. (October 2012) - Kaur, Sukhwinder; Baine, Michael J; Jain, Maneesh; Sasson, Aaron R; Batra, Surinder K
Pancreatic cancer is a lethal malignancy with its incidence almost equivalent to mortality. The complex pathophysiology, absence of early diagnostic and prognostic markers and unresponsiveness to radiation and chemotherapies are major barriers against successful therapy. Poor performance of therapeutic agents, even in the initial stage of invasive cases, emphasizes the importance of early detection for improved survival. The present review discusses the challenges and advances in biomarkers including serological signatures, circulating tumor cells, autoantibodies, epigenetic markers and miRNAs that are being explored to detect this cancer at early stages. Considering the long time gap between the development of malignant lesions and full-blown primary and metastatic pancreatic cancer, unique opportunities are being contemplated for the development of potential diagnostic and prognostic markers.